2022
DOI: 10.1002/jbm.b.35060
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric resorbable‐based dental barrier membrane for periodontal guided tissue regeneration and guided bone regeneration: A review

Abstract: Guided tissue regeneration (GTR) and guided bone regeneration (GBR) are two common dental regenerative treatments targeted at reconstructing damaged periodontal tissue and bone caused by periodontitis. During GTR/GBR treatment, a barrier membrane is placed in the interface between the soft tissue and the periodontal defect to inhibit soft tissue ingrowth and creating a space for the infiltration of slowgrowing bone cells into the defect site. Recently, asymmetric resorbable-based barrier membrane has received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 168 publications
0
35
0
Order By: Relevance
“…Studies have shown that barrier membranes are crucial for proper bone regeneration during the GBR process, as they need to occlude the faster growing soft tissue to invade into the bone defect underneath, thus providing the appropriate space, time for the comparatively less slowly growing bone tissue to regenerate 4 . To achieve optimal bone regeneration, GBR membranes should possess good biocompatibility, proper mechanical characteristics for space maintenance, ideal resorption time to prevent epithelial cell migration into the bone defect and provide enough time for bone regeneration, and the ability to stimulate bone formation 5,6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that barrier membranes are crucial for proper bone regeneration during the GBR process, as they need to occlude the faster growing soft tissue to invade into the bone defect underneath, thus providing the appropriate space, time for the comparatively less slowly growing bone tissue to regenerate 4 . To achieve optimal bone regeneration, GBR membranes should possess good biocompatibility, proper mechanical characteristics for space maintenance, ideal resorption time to prevent epithelial cell migration into the bone defect and provide enough time for bone regeneration, and the ability to stimulate bone formation 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…Absorbable membrane does not bring additional trauma to the patients. The key factors affecting the usage of absorbable membranes include absorbing rate, compatibility, rigidity, porosity, and so forth 5 . Synthetic absorbable polymers including members of aliphatic polyesters and their copolymers have been used as GBR membranes, including poly lactic acid and poly lactic‐co‐glycolic acid 11,12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Upon immersion of the casting solution in the coagulation bath, the interfacial surface is exposed to the coagulant. The exchange rate of solvent and coagulant is so high that the polymer precipitation and solidifying happen almost concurrently, which leads to the generation of a dense skin layer on the top surface [ 38 , 39 ]. On the other hand, the weak affinity of the PSF to water as the nonsolvent results in a shorter time of solvent exchange and a greater exchange rate caused by the larger finger-shape pores [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, pore size is closely related to both the cell occlusive property and PDL/bone regeneration. Previous studies have demonstrated that macroporous design (pore size > 100 μm) is favorable to provide adequate space for osteogenesis cell ingrowth, which leads to greater bone regeneration compared to microporous membrane [40,41]. However, as for barrier functionality, it has been reported that membranes with pores size exceeding 100 μm may permit soft-tissue invasion [42].…”
Section: Discussionmentioning
confidence: 99%
“…2K). Moreover, it is well agreed that the barrier biomaterials should be biocompatible with the endogenous cells to support tissue healing process [40]. GelMA and Si-HPMC are both biodegradable and injectable hydrogel that is nontoxic, and have been widely studied for tissue engineering or drug delivery applications [49,50].…”
Section: Discussionmentioning
confidence: 99%